“Subpial Fan Cell” — A Class of Calretinin Neuron in Layer 1 of Adult Monkey Prefrontal Cortex - Gabbott, Paul L. A. (Frontiers in Neuroanatomy, 2016)
Layer 1 of the cortex contains populations of neurochemically distinct neurons and afferent fibres which markedly affect neural activity in the apical dendritic tufts of pyramidal cells. Understanding the causal mechanisms requires knowledge of the cellular architecture and synaptic organisation of layer 1. This study has identified 8 morphological classes of calretinin immunopositive (CRet+) neurons (including Cajal-Retzius cells) in layer 1 of the prefrontal cortex (PFC) in adult monkey (Macaca fasicularis), with a distinct class - termed ‘subpial fan (SPF) cell’ - described in detail. SPF cells were rare horizontal unipolar CRet+ cells located directly beneath the pia with a single thick primary dendrite that branched into a characteristic fan-like dendritic tree tangential to the pial surface. Dendrites had spines, filamentous processes and thorny branchlets. SPF cells lay millimetres apart with axons that ramified widely in upper layer 1. Such cells were GABA immunonegative (-) and occurred in areas beyond PFC. Interspersed amidst SPF cells displaying normal structural integrity were degenerating CRet+ neurons (including SPF cells) and clumps of lipofuscin-rich cellular debris. The number of degenerating SPF cells increased during adulthood. Ultrastructural analyses indicated SPF cell somata received asymmetric (A - presumed excitatory) and symmetric (S - presumed inhibitory) synaptic contacts. Proximal dendritic shafts received mainly S-type and distal shafts mostly A-type input. All dendritic thorns and most dendritic spines received both synapse types. The tangential areal density of SPF cell axonal varicosities varied radially from parent somata - with dense clusters in more distal zones. All boutons formed A-type contacts with CRet- structures. The main post-synaptic targets were dendritic shafts (67%; mostly spine-bearing) and dendritic spines (24%). SPF-SPF cell innervation was not observed. Morphometry of SPF cells indicated a unique class of CRet+/GABA- neuron in adult monkey PFC – possibly a subtype of persisting Cajal-Retzius cell. The distribution and connectivity of SPF cells suggest they act as integrative hubs in upper layer 1 during postnatal maturation. The main synaptic output of SPF cells likely provides a transminicolumnar excitatory influence across swathes of apical dendritic tufts - thus affecting information processing in discrete patches of layer 1 in adult monkey